The Elderly and Hoaxes within the Sphere of Indonesian Democracy in the Digital Age - Faizah, Nur (Jurnal Studi Multidisiplin Qomaruna, 2023)
The presence of social media has become an essential part of daily life, including for elderly people. However, the spread of hoaxes and fake news on social media can have serious consequences, particularly for the elderly who may be more vulnerable to misinformation. The article highlights the dangers of hoaxes, particularly in the context of political campaigns, and their potential impact on the elderly's voting choices. The article also discusses the importance of media literacy for the elderly, particularly in the era of digital media where it can be challenging to distinguish between fact and fiction. Through literature studies, the article highlights the real-life implications of hoaxes for the elderly and underscores the need for media literacy to combat hoaxes in the digital era.